At the Loch: a library proposal for the Boleskine house foundation - Klint, Georg (My University, 2021)
At the eastern shores of Loch Ness, Scotland, Boleskine House is found. This is a manor built in 1809 with an interesting and controversial history, most noticeable for having been owned by Aleister Crowley and Jimmy Page of Led Zeppelin. Since 2019 the area is owned by the Boleskine House Foundation, which is a non-profit organization whose main aim is to restore and maintain the Boleskine House estate. Their end goal and overall vision for Boleskine House is that it will become a historical landmark that will offer public accessibility and enjoyment in a way hitherto unavailable, including a forum that will enrich people with the importance of history and heritage. Therefore, the foundation has future plans to build a library on site. The focus of the library will be local Scottish history but also the contested topic of western esotericism. This thesis presents a design proposal for how a library on this site could look like, and what qualities it would offer. The aim of the thesis is to show how architecture can relate to place and history, but also how it can facilitate reading and learning. Incorporating the concept of a lightbringer and the theory of analogue architecture, the design proposal is based upon traditional site analysis as well as studies of the library typology through literature and drawn reference projects. The library is situated on the same lot as Boleskine House and its restored formal garden which means that it has to relate to the existing architecture, while at the same time also act as a public building on site. The interior spaces include a book collection of 25 000 volumes as well as a small archive and spaces for reading, working and recreation.
Keywords: Library architecture, contextual architecture, analogue architecture, Loch Ness, iconography